2001
DOI: 10.3109/13682820109177864
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality of Life in People With Aphasia the Stroke Specific Quality of Life Scale

Abstract: Assessing health related quality of life (HRQOL) in people with communication disabilities is a challenge in health related research. Materials used to assess HRQOL are often linguistically complex and their mode of administration usually does not facilitate people with communication disabilities to give their experiences. We are currently running a medium scale study (80 participants) which aims to explore the HRQOL of people with long-term aphasia and to assess the psychometric properties and the acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 14 publications
0
58
0
Order By: Relevance
“…Established methods were adopted 15,16,17 : large font (minimum 14), key words in bold, few items per page, and where appropriate pre-prepared pictures were used i .…”
Section: Methodsmentioning
confidence: 99%
“…Established methods were adopted 15,16,17 : large font (minimum 14), key words in bold, few items per page, and where appropriate pre-prepared pictures were used i .…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing literature describing methods of increasing communicative access for people with aphasia (e.g., Alarcon & Rogers, 2010;Kagan, Black, Duchan, Simmons-Mackie, & Square, 2001;Simmons-Mackie, Kagan, O ' Neill Christie, Huijbregts, McEwen, & Willems, 2007). For example, characteristics of aphasia-friendly printed materials and supports have been described (e.g., Hilari & Byng, 2001;Kagan, 1998;Rose, Worrall, & McKenna, 2003;Worrall, Rose, Howe, Brennan, Egan, Oxenham, et al, 2005). The ALA was designed with these principles in mind and in keeping with extensive experience in Supported Conversation for Adults with Aphasia (SCA TM ), a method designed to facilitate communication with people with aphasia (Kagan, 1998).…”
Section: Development Of the Assessment For Living With Aphasiamentioning
confidence: 99%
“…In the literature, however, not many studies about aphasics QOL can be found, mainly due to difficulties on the part of the interviewers in dealing with linguistic-cognitive impairments, and also difficulties on the part of the patients in understanding and expressing themselves in a satisfactory way to convey their actual QOL (3,4,14,15) . For this reason, some authors (3,14) point out the need to adapt the QOL questionnaires to favor the participation of the aphasics, by, for example, simplifying the questions and using pictures.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some authors (3,14) point out the need to adapt the QOL questionnaires to favor the participation of the aphasics, by, for example, simplifying the questions and using pictures.…”
Section: Introductionmentioning
confidence: 99%